2015
DOI: 10.3389/fnbeh.2015.00149
|View full text |Cite
|
Sign up to set email alerts
|

Dscam2 affects visual perception in Drosophila melanogaster

Abstract: Dscam2, a cell surface protein that mediates cellular repulsion, plays a crucial role in the development of the Drosophila melanogaster visual system. Dscam2 generates boundaries between neighboring modules in the fly optic lobe; in Dscam2 mutants this visual system modularity is compromised. Although developmental wiring defects have been well described in the Dscam2 mutant, behavioral consequences have not been investigated. To address this, we examined the visual behavior of Dscam2 mutant flies. Using a pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 40 publications
(60 reference statements)
0
12
0
Order By: Relevance
“…In phototactic experiments our wild-type flies preferred the blue-lit arm of the T-maze, as previously reported ( Jacob et al, 1977 ). However, Drosophila 's attraction to blue light has not always been observed and some studies report instead a green preference ( Bosch et al, 2016 ). Regardless, the phototactic responses of inebriated suggest that this mutant is not, in fact, blind.…”
Section: Discussionmentioning
confidence: 99%
“…In phototactic experiments our wild-type flies preferred the blue-lit arm of the T-maze, as previously reported ( Jacob et al, 1977 ). However, Drosophila 's attraction to blue light has not always been observed and some studies report instead a green preference ( Bosch et al, 2016 ). Regardless, the phototactic responses of inebriated suggest that this mutant is not, in fact, blind.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that L4 neurons play a key role motion processing, resolving previous contradictory studies on its function (Meier et al, 2014). It was also found that visual circuit miswiring in the absence of Dscam2 leads to specific and conditional differences in visual acuity (Bosch et al, 2015). Strikingly, in three of the behavioral paradigms tested, Dscam2 mutants showed an opposing response as wild-type flies.…”
mentioning
confidence: 93%
“…When a group of flies is placed in a tube and subjected to a moving grating perpendicular to the tube, the flies move against the direction of motion (Lee et al, 2001, Zhu & Frye, 2009; figure 1.2A/B). In contrast, populations of flies walking through an 8-tiered maze (figure 1.2C), single free walking flies in a paper/plastic striped drum (figure 1.2D) or tethered flies (figure 1.2E-F) move in the direction of the moving grating (Blondeau & Heisenberg, 1982, Bosch et al, 2015, Buchner, 1976, Evans et al, 2011, Götz, 1968, Götz & Wenking, 1973, Mccann & Macginitie, 1965, Van Swinderen & Flores, 2007. Why the optomotor response is assay-dependent is not known, and this thesis will provide new insight into this problem using both population and single fly assays.…”
Section: Motion Detection 131 Optomotor Responsementioning
confidence: 99%
“…Previous research demonstrated that in single choice population assays, a group of mixed gender flies walked in the opposite direction of the moving grating (Lee et al, 2001, Zhu & Frye, 2009. In the population assay described in this chapter, flies have to make a multitude of left/right choices while exposed to a moving grating and female flies respond by following the moving grating (Bosch et al, 2015, Evans et al, 2011, Van Swinderen & Flores, 2007.…”
Section: Comparison Between a Population And Single Fly Assaymentioning
confidence: 99%
See 1 more Smart Citation